The Efficacy of Blended Learning in Enhancing Oral Proficiency in Aviation School: An In-depth Investigation - Sylvia, Tiara; Rochmawati, Laila; Diriyanti Novalina, Susi (JEES (Journal of English Educators Society), 2024)
Blended learning has been identified as a highly promising instructional approachwithin vocational education institutions. The objective of this study is to examine the disparities in speaking skills learning strategies between traditional (face-to-face) instruction and blended learning. Additionally, the study seeks to ascertain the impact of these learning strategies on students' speaking abilities in both traditionaland blended learning environments. The present study employs a quantitativeresearch approach, utilizing an experimental design. The sample for this studycomprised 120 participants, 24 participants representing Politeknik PenerbanganMedan and 96 participants representing Politeknik Penerbangan Surabaya. Theresults of this study suggest that the mere adoption of technology and the removalof the traditional classroom setting do not suffice in establishing an optimal learningenvironment for individuals learning a second or foreign language. Nevertheless,there exists a considerable opportunity to amalgamate conventional educationalsettings with contemporary technological advancements in order to enhancestudents' academic achievements across various abilities and sub-skills, with aparticular emphasis on oral communication proficiency. Based on the resultsobtained from the study, it is possible to draw the following conclusions: 1) Astatistically significant disparity exists in the proficiency of English speaking skillswhen employing the blended learning approach. 2) A statistically significantdiscrepancy is observed in the proficiency of English speaking skills for theexperimental group, thereby corroborating the efficacy of post-implementationlearning strategies. HIGHLIGHTS : The experimental group demonstrated significant improvements in various aspects of speaking skills,leading to a notable increase in mean speaking ability scores from pre-test to post-test, indicating anoverall enhancement of 11.80%. Conversely, the control group showed minimal improvements,reflecting a minor increase in pre-test to post-test scores. The ANOVA test results revealed no statistically significant difference in the mean initial ability scorebetween participants exposed to blended learning techniques and those receiving traditional methodsfor the pretest. However, for the posttest, a significant difference was observed, suggesting thatblended learning approaches significantly enhanced final ability scores compared to traditionalmethods. Blended learning, facilitated by multimedia sources like E-Module Aviation Speaking PreparationTest, creates a conducive learning environment and improves independent learning strategies,ultimately enhancing students' speaking achievements. Incorporating blended learning approaches in language education can lead to better learning outcomes and enhanced language proficiency, supportedby previous research demonstrating the benefits of blended learning over face-to-face teaching.Providing online resources can add value to students and improve their performance, particularly inspeaking lessons tailored to meet students' needs and interests.